The Effect Of Competence, Career Path Improvement And Job Satisfaction On Nurse Performance At Premier Bintaro Hospital - Ekantiana, Evy; Madiistriyatno, Harries; Hasudungan, Eddy Hermawan (SEAN Institute, 2024)
The objectives of this study: 1) To find out and analyze the influence of competence on the performance of Premier Bintaro Hospital nurses. 2) To find out and analyze the Effect of Professional Career Path Improvement on the Performance of Premier Bintaro Hospital Nurses 3) To find out and analyze the Effect of Job Satisfaction on the Performance of Premier Bintaro Hospital Nurses. 3 To find out and analyze the influence of Competence, Professional Career Path Improvement and Job Satisfaction together on the Performance of Premier Bintaro Hospital Nurses. This research is a quantitative research, descriptive and associative. The population in this study is 249 nurses at Premier Bintaro Hospital. The sampling technique used was a sample using the Slovin formula, a sample of 71 nurses at Premier Bintaro Hospital was taken as respondents in this study. The results in this study: 1) Based on the coefficients table, the tcal value for the Competency variable (X1) is 3,237 while the t-value of the table for n = 71 is 1,993. So 3,237 > 1,993, then H0 is rejected and Ha is accepted, it can be stated that Competence (X1) affects the Performance of Nurses (Y) at Premier Bintaro Hospital. 2) Based on the coefficients table, the tcal value for the Career Path Improvement variable (X2) is 4,759, while the t-valueof the table for n = 71 is 1,993, so 4,759 > 1,993, then H0 is rejected and Ha accepted, it can be stated that Career Path Improvement (X2) affects Nurse Performance (Y) at Premier Bintaro Hospital. 3) Based on the coefficients table, the tcal value for the Job Satisfaction variable (X3) is 4.943, while the t-valueof the table for n = 71 is 1.993, so 4.943 > 1.993, then H0 is rejected and Ha is accepted, it can be stated that Job Satisfaction (X3) affects the Performance of Nurses (Y) at Premier Bintaro Hospital. 4) Based on the results of the analysis in the table namely the ANOVA test obtained an Fcal value of 45.357 while the Ftable (α 0.05) for n = 71 was 2.50. So Fcalculate > from the Ftable (α 0.05) or 45,357 > 2.50, with a significant level of 0.000 because 0.000 < 0.05, then it can be said that Competence (X1), Career Path Improvement (X2) and Job Satisfaction (X3) together affect Nurse Performance (Y).